Pemanfaatan Limbah Organik Cair pada Tanaman Apotik Hidup untuk Meningkatkan Kreativitas Siswa SMA Negeri 2 Pemalang pada Konsep Pencemaran Lingkungan - Imam Khazali; Joko Siswanto (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2020)
The purpose of this study was to determine the use of liquid organic waste in live pharmacy plants to enhance student creativity in the concept of environmental pollution. The implementation of this research was conducted at SMAN 2 Pemalang. The research method used is quantitative descriptive. The sample used consisted of one class, class XI IPA 1 as an experimental class with a total of 30 students. The research parameters measured included students' creative thinking which included aspects: think fluently, think flexible, think original, and think elaboration. From the results of data analysis and discussion, it was concluded that the creative thinking of XI IPA 1 students of SMAN 2 Pemalang was 5.70. (5.70%) of the maximum score of 40. If seen from the ability based on Fluency indicators 1.13 (37.5 %), Flexibility 1.10 (36.67%), Originality 1.08 (35.83%), and Elaboration 0.98 (32.50%).